4-1BBL enhances CD8+ T cell responses induced by vectored vaccines in mice but fails to improve immunogenicity in rhesus macaques. - Alexandra J Spencer; Julie Furze; Jared D Honeycutt; Alice Calvert; Saroj Saurya; Stefano Colloca; David H Wyllie; Sarah C Gilbert; Migena Bregu; Matthew G Cottingham; Adrian V S Hill (PLoS ONE)
T cells play a central role in the immune response to many of the world's major infectious diseases. In this study we investigated the tumour necrosis factor receptor superfamily costimulatory molecule, 4-1BBL (CD137L, TNFSF9), for its ability to increase T cell immunogenicity induced by a variety of recombinant vectored vaccines. To efficiently test this hypothesis, we assessed a number of promoters and developed a stable bi-cistronic vector expressing both the antigen and adjuvant. Co-expression of 4-1BBL, together with our model antigen TIP, was shown to increase the frequency of murine antigen-specific IFN-γ secreting CD8(+) T cells in three vector platforms examined. Enhancement of the response was not limited by co-expression with the antigen, as an increase in CD8(+) immunogenicity was also observed by co-administration of two vectors each expressing only the antigen or adjuvant. However, when this regimen was tested in non-human primates using a clinical malaria vaccine candidate, no adjuvant effect of 4-1BBL was observed limiting its potential use as a single adjuvant for translation into a clinical vaccine.